CSR AND ORGANIZATIONAL PERFORMANCE: A THEORETICAL MODEL - Ali, A.R.S. Ibn; Rana, Md Jowel; Nahar, Shamsun; Tesha, N Hosna Ara; Jabir, Imtiaz Md Shihab (American International Journal of Multidisciplinary Scientific Research, 2022)
Nowadays, the market is very competitive due to rapid digitalization and globalization where the sustainability of every business depends on organizational performance. The better performance of the company relies on corporate social responsibility which helps to create goodwill in the fierce market. Corporate social responsibility is a crucial issue for every organization to develop the performance that assists to stay in the aggressive market. Basically, organizational performance depends on the reputation of the organization which moderates the relationship between customers, community, and employees’ in organizational performance. The main objective of this study is to reveal the contributions of corporate social responsibility’s dimension on organizational performance. Data have been collected from different sources like the Scopus database, Google Scholar, Research gate, ABDC, emerald, etc. The major dimensions of CSR are community, customers, employees, organizational commitment, and reputation which have significant and positive impacts on organizational performance. For this study purpose, the dimensions of CSR are adopted from the previous extensive literature review. In this study, the conceptual model has been proposed based on the previous literature. This study could help to corporate managers to maintain organizational performance through corporate social responsibility (CSR).JEL Classification Codes: L25, M14, L32.